RASA TERBAKAR DI MULUT PADA PEMAKAIAN GIGI TIRUAN - Fransiska Nuning Kusmawati (Universitas Baiturrahmah, 2015)
Burning sensation in the mouth is a condition that is characterized by spontaneous burning or uncomfortable feeling in the mouth without being followed by the real cause. The predisposing factors are divided into three factors : local factors, systemic and psychogenic. The use of denture is a local predisposing factor of burningsensation in the locally in the mouth. The treatments were performed in patients with a burning sensation in the mouth are is a top priority. Management steps in patient burning sensation in the mouth, are to, find the local etiology factors in oral or systemic and then traet the patient according to the cause.